Phase Contrast Imaging Based Microbubble Monitoring of Radiofrequency Ablation: An ex vivo Study - Huang, Wei; Lu, Jian; Tang, Rongbiao; Wu, Zhiyuan; Wang, Qingbing; Ding, Xiaoyi; Wang, Zhongmin; Chen, Kemin (Frontiers in Oncology, 2020)
Background To explore the potential of synchrotron radiation phase contrast imaging for real-time microbubble formation monitoring during radiofrequency ablation. Methods Radiofrequency ablation was performed on ex vivo porcine muscle tissue using unipolar and multi-tined expandable electrodes. Images of microbubble formation in the samples were captured by both synchrotron radiation phase contrast imaging and absorption contrast imaging. The synchronous ablation temperature was recorded. Each RFA electrode type group contained 6 samples. Ablation size was assessed by histologic examination. Results Microbubble formation during radiofrequency ablation could be visualized by synchrotron radiation phase contrast imaging. The diameter of the microbubbles revealed on the image ranged from tens of microns to several millimetres, and these microbubbles first appeared at the edge of the RFA electrode when the target region temperature reached approximately 60℃ and rapidly extended outwards. The average microbubble range measured on PCI was 17.66±0.74 mm. The average range of coagulation necrosis measured by histological examination was 17.22±0.38 mm. There was no significant difference between them (P>0.05). The range of microbubbles corresponded to the ablation zone. Conclusions Phase contrast imaging enabled real-time high-resolution visualization of microbubble formation during radiofrequency ablation, indicating a potential for its use in ablation monitoring.